2022
DOI: 10.1186/s12954-022-00656-y
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of naloxone opioid overdose awareness and reversal training for first-year medical students: specific elements require reinforcement

Abstract: Background The opioid epidemic is a progressively worsening public health crisis that continues to impact healthcare system strategies such as overdose reversal and destigmatization. Even among healthcare professionals, there remains a lack of confidence in naloxone administration and a prevalence of stigma. While training can play a major impact in reducing these shortcomings, the long-term effectiveness has yet to be characterized in training healthcare professionals. This study examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Nonetheless, we hypothesize that the decrease in subjective preparedness to respond to an overdose may have arisen from students' increased awareness about knowledge gaps and potential risks of naloxone (e.g., precipitated withdrawal). This finding echoes that of Sandhu et al, 38 who found regression of improvement in confidence about responding to an opioid overdose 3 months after an OOPR training, a finding they attributed to students' self‐awareness of knowledge lost. This knowledge awareness could foster agreement with limiting naloxone access because students also indicated concern that patients should receive guidance and information before receiving multiple naloxone doses.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nonetheless, we hypothesize that the decrease in subjective preparedness to respond to an overdose may have arisen from students' increased awareness about knowledge gaps and potential risks of naloxone (e.g., precipitated withdrawal). This finding echoes that of Sandhu et al, 38 who found regression of improvement in confidence about responding to an opioid overdose 3 months after an OOPR training, a finding they attributed to students' self‐awareness of knowledge lost. This knowledge awareness could foster agreement with limiting naloxone access because students also indicated concern that patients should receive guidance and information before receiving multiple naloxone doses.…”
Section: Discussionsupporting
confidence: 87%
“…Nonetheless, we hypothesize that the decrease in subjective preparedness to respond to an overdose may have arisen from students' increased awareness about knowledge gaps and potential risks of naloxone (e.g., precipitated withdrawal). This finding echoes that of Sandhu et al, 38 who found regression of improvement in confidence about would be useful and less than a third thought they would use the waiver. These findings align with existing physician buprenorphine prescribing behavior.…”
Section: Total Indicating This Reason Total Indicating This As Primar...supporting
confidence: 85%
“…Similar data has been seen when looking at non‐pharmacy students. Sandhu and colleagues 19 described naloxone training for first‐year medical students using opioid overdose awareness and reversal training, an educational method detailed in the medical education literature as being effective in increasing naloxone prescribing rates 20 . A survey that assessed student knowledge and perceived self‐efficacy in responding with naloxone was administered immediately following the training and again 3 months later.…”
Section: Discussionmentioning
confidence: 99%
“…Naloxone training is a brief, educational harm reduction intervention comprised of distribution of naloxone alongside information about opioids, safer drug use, overdose risk and symptoms, and medication administration. [17][18][19] These trainings have been found to significantly increase knowledge regarding safer substance use amongst people who use drugs, service providers, and the public. [17][18][19] Naloxone can reverse a potentially fatal opioid overdose and can be administered by anyone, [17][18][19] however training is required to ensure proper implementation.…”
Section: Iiia Implications For Harm Reductionmentioning
confidence: 99%
“…[17][18][19] These trainings have been found to significantly increase knowledge regarding safer substance use amongst people who use drugs, service providers, and the public. [17][18][19] Naloxone can reverse a potentially fatal opioid overdose and can be administered by anyone, [17][18][19] however training is required to ensure proper implementation. 18 Additionally, harm reduction peer support groups will be offered by APSS to active drug users that focus on psychoeducation, enhancing participant support networks, and knowledge of safer drug use.…”
Section: Iiia Implications For Harm Reductionmentioning
confidence: 99%